PENYELESAIAN HUTANG YANG DIALIHKAN SECARA TAKE OVER DENGAN AKAD MUSHARAKAH DI BRI SYARIAH KCP DIPONEGORO SURABAYA - Uswatun Chasanah (Maliyah : Jurnal Hukum Bisnis Islam, 2014)
Basically, the pattern of relationships built between the customer and the bank is symbiosis mutualism, which is mutually beneficial relationship, where the bank according to function the collecting and distributing public funds to improve the lives of many people, especially the Islamic Banking not only prioritize mutually beneficial transaction, but more than that, pengoprasionalan Islamic Bank can not escape the principle of helping others, especially the settlement of debts. Debt settlement is transferred to take over the contract musha>rakah is the removal of the rest of the debt held by customers of Financial Institutions Shari’ah or Islamic Financial Institutions to other Islamic Bank with contract qard}, next to Bank Syariah customer debt settled with agreement musha>rakah , in which each party contributes funds (or charitable/expertise) with the agreement that the benefits and risks will be shared in accordance with the agreements. According to Islamic law, debt settlement is transferred to take over the contract musha>rakah in BRI Syariah KCP Diponegoro Surabaya does not conflict with Islamic law because the parties have been implementing harmonious and terms and conditions are in accordance with Islamic law, so that such transactions are allowed in Islam.